Building performance evaluation of public housing in Harare, Zimbabwe - Ignatius Morgen Chombo (University of the Free State, 2021)
This study sought to evaluate the performance of residential building spaces in public housing in Harare, Zimbabwe. It specifically measured building performance indicators determined by the building’s characteristics and the physical, locational and service attributes of buildings. A quantitative research design was adopted, in which questionnaires and observations were used in data collection. A two-stage sampling technique was used, because the population could be subdivided into clusters. From residents in three clusters, which include Highfield-Venice Flats, Avenues Flats and Mbare Flats, 263 respondents were conveniently chosen. Results from the independent t-test that was conducted showed that, at 95% confidence level, there exist significant differences in residential satisfaction among residents of Highfield-Venice Flats and those of Avenues Flats (t = 2.159, p-value= 0.035>0.05). Overall, residents are dissatisfied with the attributes of the buildings in which they live and the general residential situation. There is a general dissatisfaction with the buildings, suggesting that the building performance is not meeting their needs and expectations. Housing attribute preferences, privacy, dwelling proximity, and neighbourhood attachment showed a significant and positive impact on general residential satisfaction. Hence, there is a need to improve housing attribute preferences such as improving the quality of air and lighting as well as noise levels, since respondents expressed dissatisfaction with these attributes. Housing ceilings can be installed to reduce noise levels. More so, the quality of air and lighting can be improved by inserting more air ventilations and wider windowpanes. Privacy should be improved by ensuring that the residential structures have boundary walls that may be needed by the residents. More so, dwelling proximity ought to be improved. The Ministry of National Housing and Social Amenities and other public housing institutions can consider developing structures such as shopping centres, public schools as well as roads and social amenities such as parks, pools and workout facilities before they build residential houses.